Kepuasan Kerja Vs Ketidakpuasan Kerja Pada ASN di Rupbasan: Sebuah Studi Kualitatif - Novia Christine Feoh (ManBiz: Journal of Management and Business, 2025)
This study explores the factors influencing job satisfaction and dissatisfaction among Civil Servants at the State Storage House. Utilizing a qualitative approach, in-depth interviews were conducted with 5 employees through semi-structured interview guides, followed by thematic analysis of the transcribed interviews. The findings reveal that job satisfaction is driven by internal factors such as leadership, coworker relationships, and personal values, while dissatisfaction arises from external factors including perceived injustice, limited public support, and restrictive regulations. The study highlights the complex dynamics of job satisfaction, influenced by interactions between internal and external factors. These findings suggest the need for supportive policies, regulatory improvements, and enhanced public recognition to foster a conducive work environment for Rupbasan employees' well-being. Keywords: Civil Servants, Job Satisfaction , Leadership, Regulation, State Storage House